A Research on Goat milk and Papaya Face Wash - Sohel K. Shaikh; Minakshi Khairnar; Ganesh Ahire; Aakanksha Dashpute; Varsharani Pawar; Monali Patil (Recent Trends in Cosmetics, 2026)
The increasing demand for natural and sustainable skincare products has driven interest in bio-based cosmetic formulations. This study focuses on the development and evaluation of a goat milk and papaya–based face wash aimed at providing gentle cleansing, moisturizing, and exfoliating properties through natural ingredients. Goat milk, rich in lactic acid, proteins, and essential fatty acids, contributes to hydration and mild exfoliation, while papaya (Carica papaya) extract, containing papain enzyme and vitamins A and C, promotes skin renewal and brightening. The formulation was optimized for pH balance, stability, and sensory characteristics. Physicochemical parameters such as viscosity, foaming capacity, spread ability, and microbial stability were assessed according to cosmetic formulation standards. Additionally, preliminary dermatological testing evaluated for skin compatibility and cleansing efficacy. The results indicated that the goat milk and papaya face wash maintained a stable emulsion and with acceptable organoleptic properties and demonstrated mild cleansing with minimal irritation potential. The combination of natural bioactive offers a promising alternative to synthetic surfactant-based cleansers, supporting the development of safe, eco-friendly, and effective skincare products.
Keywords: Goat milk; Natural cosmetics; Papain; Papaya; Skin care